Resources, capabilities and competences for eco-innovation - Del Río, Pablo; Carrillo-Hermosilla, Javier; Könnölä, Totti; Bleda, Mercedes (Technological and Economic Development of Economy, 2016)
The existing literature on the determinants for the development and adoption of ecoinnovations has generally focused on analysing the influence of business strategies and external drivers (public policy and stakeholder impacts) on innovation processes in firms. Internal factors to the firm such as resources, capabilities and competences (RCCs), which are important drivers of business strategies and innovation performance, are seldom considered in the literature. This paper builds an integrated framework that incorporates the impact of those firm’s internal factors and their interactions with external drivers on the development and adoption of eco-innovations. The relevance of those factors regarding several dimensions of eco-innovation is illustrated with case studies. It is shown that, while all RCCs are relevant for the development and uptake of ecoinnovations, their relevance differs across eco-innovation dimensions.First published online: 03 Nov 2015